Rol de los padres de familia y su influencia en el proceso de aprendizaje de los niños de 5to de EGB en la UE Emigdio Esparza Moreno, Babahoyo. 2022 - Carriel Laje, Daniela Mercedes (2022)
The present study deals with the role of parents and their influence on the learning process of children; the current context in which society lives demands this research because parents are immersed in multiple activities and sometimes neglect the academic support that their children demand. The study has a qualitative-quantitative approach, in which the types of documentary and field research were used to academically support the criteria issued throughout the study; the selected sample are 30 parents of students attending parallel A of the 5th year of EGB in the UE Emigdio Esparza Moreno, to whom a survey was applied to obtain a general description of the current situation. The results show that, although most parents are aware of the importance of providing effective accompaniment to their children, they do not set aside quality time to be attentive to their children's learning. The conclusions of the research are that the role of the parents does influence the learning of the children, since those who show better averages are those who have a better academic accompaniment from their parents.